Global prevalence of hydrocele in infants and children: a systematic review and meta-analysis - Nader Salari; Mahan Beiromvand; Reza Abdollahi; Fuzieh Khani Hemmatabadi; Alireza Daneshkhah; Amirhoussain Ghaderi; Maryam Asgari; Masoud Mohammadi (BMC Pediatrics)
Abstract Background Pediatric hydrocele is a congenital pathology commonly diagnosed in newborns. Also, untreated pediatric hydrocele can induce adverse permanent consequences in adulthood. This study aimed to investigate the global prevalence of pediatric hydrocele in infants and children, as a necessary factor for health policymakers. Methods Databases of PubMed, Scopus, Web of Science, Embase, ScienceDirect, and Google Scholar search engine were systematically searched for studies reporting the prevalence of pediatric hydrocele in infants and children. The main keywords of “Prevalence”, “Outbreak hydrocele”, “Infant”, and “Child” were used in this regard. Screenings were applied to achieve eligible papers and a quality control process was conducted to select middle to high-quality papers. Finally, the random effect model was used to perform meta-analysis, and heterogeneity was checked by the I2 index. Data analysis was applied with CMA (v.2) software. Results Following the assessment of 5 eligible studies with a sample size of 70,961 infants (1–2 weeks), the global prevalence of hydrocele in infants was found 0.001% (95%CI:0.00007–0.018, 1 per 1000 live births). In the review of 3 studies with a sample size of 278,597 children (7–12 years), the global prevalence of hydrocele in children was reported 0.0034% (95%CI:0.00004–0.21), 3.4 per 1000 children). Conclusion According to the analyzed studies, a relatively high prevalence of hydrocele in infants was reported, globally. Besides, there were undiagnosed or recurrent pediatric hydrocele cases in children which need more precise medical screening. Thus, it is necessary to implement health policies to reduce the prevalence of pediatric hydrocele and associated adverse consequences.